2016
DOI: 10.1016/j.pecs.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Heat and fluid flow in high-power LED packaging and applications

Abstract: Light-emitting diodes (LEDs) are widely used in our daily lives. Both light and heat are generated from LED chips and then transmitted or conducted through multiple packaging materials and interfaces. Part of the transmitted light converts into heat along the light propagation; in return, the accumulation of heat leads to the degradation of light output. The accumulated heat negatively influences the reliability and longevity of LEDs, and thus thermal management is critical for LED packaging and applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 402 publications
(121 citation statements)
references
References 267 publications
0
121
0
Order By: Relevance
“…But the weakened thermal reflection effect could be improved with thinnerlayer structures or larger layer number N. 20 It is demonstrated that the present thermal reflection meta-device can also be made by nature-existing isotropic materials. With directional heat transfer, the present meta-device could be used to realize local heating/cooling for electronic devices 34 and high-efficient energy harvesting/utilizing.…”
Section: Resultsmentioning
confidence: 99%
“…But the weakened thermal reflection effect could be improved with thinnerlayer structures or larger layer number N. 20 It is demonstrated that the present thermal reflection meta-device can also be made by nature-existing isotropic materials. With directional heat transfer, the present meta-device could be used to realize local heating/cooling for electronic devices 34 and high-efficient energy harvesting/utilizing.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 According to literature, 31 YAG:Ce-silicone white phosphor-converted LEDs can withstand phosphor luminance levels of up to 1e6 cd∕m 2 without undergoing thermal quenching in the steady state. In our device, the luminance reaches a maximum value of 2.2e5 cd∕m 2 , hence, no thermal quenching is expected to occur.…”
Section: Spot Phosphor Concept Activated Bymentioning
confidence: 99%
“…[4][5][6][7][8] In general, there are interactions among these photometric, electrical, and thermal aspects. [9][10][11][12] In their works, the photo-electro-thermal theory has been presented by linking the luminous flux, thermal resistance, electrical current, junction temperature, heat dissipation coefficient, etc. Here, by studying theories of spontaneous emission rates and carrier recombination mechanisms, we derive a simple and useful model only linking the optical powers, junction temperatures or heat-sink temperatures, and current densities.…”
Section: Introductionmentioning
confidence: 99%